Disclosure of Local Government Social Responsibility Through GRI Reporting Standards: A Case Study of Bengkulu Province - Nata, Kalindra; Aziza, Nurna (Dinasti Publisher, 2025)
This study explores the role of sustainability reporting based on the Global Reporting Initiative (GRI) in disclosing the social responsibility of the Bengkulu Provincial Government, a region with relatively low welfare levels. Using a qualitative approach and content analysis method on official government documents, the study assesses the extent to which GRI standards are used to reflect transparent and accountable governance practices. The findings reveal that although some GRI principles have been applied, disclosures remain limited, particularly in areas such as the protection of non-civil servant labor, non-discrimination principles, and accessibility of reports to the public. The study emphasizes the importance of a systematic reporting framework in the public sector and suggests strengthening regional institutional capacity and national policies that promote comprehensive GRI implementation. By offering a perspective from the public sector in underdeveloped regions, this research contributes to the literature on sustainability reporting and opens the door for future comparative studies across provinces and mixed-method approaches.